Teologi Keadilan Allah dalam Penderitaan Manusia dan Implementasinya pada Masa Kini Berdasarkan Kitab Ayub - Kasih Situmorang; Renisha Wikawanty Lumban Raja (Jurnal Silih Asah, 2024)
The Book of Job is a work of sacred Hebrew literature that highlights the theme of inappropriate suffering. In prose narratives and poetic debates, Job attempts to understand the suffering that befell him. This article explains how Job reacts to the tests given by God, as well as the concept of God's Theology of Justice which is reflected in the dialogue between Job and God. God's justice shown to Job illustrates His authority as a just God, as well as the close relationship between truth and justice in directing humans on the right path. The implementation of the Theology of God's Justice in human suffering today emphasizes the importance of awareness of God's will and obedience to Him, as well as strengthening an intimate relationship with God in every life situation. By understanding and applying the concept of God's justice as depicted in the Book of Job, humans can uphold morality and spirituality in everyday life.